Telaah pustaka kebiasaan makan di Benua Asia termasuk Indonesia: Implikasi terhadap status gizi, epigenetik dan kesehatan - Wityadarda, Carissa; Amanda, Nadia; Immanuella, Ester Hanantika; Nurfadhilah, Andisa Alfani; Anita, Meliana Tri; Rahardianti, Syifha Nur Sallyima; Febrianti, Tamara Denisa; Siregar, Sarah Damayanti; Kinasih, Teresa Ester Sekar; Morin, Abigael Lauce; Dewi, M Falah Putra; Berliana , Yuli (ARGIPA (Arsip Gizi dan Pangan), 2025)
Dietary habits in Asia, including Indonesia, are shaped by culture, tradition, and the ongoing influence of modernization. Modernization has led to a shift from traditional diets toward the consumption of processed foods high in calories, fats, and sugars, increasing the risk of degenerative diseases such as obesity, diabetes, and cardiovascular disorders. These dietary changes also affect nutritional status and can influence gene expression through epigenetic mechanisms and genetic variation among individuals. This  tudy aims to examine dietary patterns in Asian populations and their implications for nutritional status and health through the lens of epigenetics, nutrigenomics, and nutrigenetics. This study employed a narrative literature review using a qualitative-descriptive approach. Scientific articles were gathered through Google Scholar in October 2024 using a combination of English and Indonesian keywords such as “eating habits in Asia”, “Asian dietary pattern”, “Indonesian food culture”, “epigenetics and nutrition”, “nutrigenomics in Asia”, and “nutrigenetics population”. The process involved four systematic steps: article identification, selection based on inclusion and exclusion criteria, data extraction, and thematic analysis based on geographic regions. The results show that culture and modernization significantly influence dietary patterns in Asia. Additionally, bioactive compounds found in traditional Asian foods have the potential to modulate gene expression, and genetic variations among populations may lead to different responses to the same dietary intake. This review highlights the importance of culturally tailored nutrition education and the need for population-based nutrigenetic research.